A 3D Printed Ka-Band High-Efficiency Wide-Slit Antenna Array for High-Power Microwave Applications. (23rd April 2022) - Liu, Liang; Yang, Yu; Li, Shifeng; Fang, Xianghe; Meng, Fanbao; Yu, Chuan
Abstract : A Ka-band high-power waveguide wide-slit antenna array with high efficiency and high-power capacity is proposed in this paper. The antenna uses a waveguide vertical transition structure as a part of the feed network, which improves the compactness and power capacity of the antenna. A 2 × 8 antenna array was simulated, fabricated by 3D printed technology, and measured. The measured reflection coefficient is less than −10 dB in the range of 30.4–30.9 GHz, the tested gain at 30.8 GHz is 25.8 dB, and the corresponding aperture efficiency is larger than 80%. This antenna can be applied in high-power millimeter-wave systems.